Ankylosing pelvitrochanteric heterotopic ossification in a patient with spinal cord injury - Gurcan, Serkan (BMJ Publishing Group, 2013)
Heterotopic ossification is a frequent complication after spinal cord injury. It usually develops around major weight bearing joints. However, ankylosing hip is a rare presentation. Various treatment methods have been reported and advocated as efficacious methods for management of heterotopic ossification. We report a case of ankylosing pelvitrochanteric heterotopic ossification treated with surgical excision before full maturation, postoperative radiation therapy and indomethacine without recurrence after 1 year. Treatment options are discussed in this particular case.